The place of urbanonims in the main classification of onims (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
Тhe article discusses the problem of classification of urbanonim and offers the own system of classification.
Keywords: urbanonimic space; urbanonim; toponim; toponimіс space; onim